Marketing Analysis: The Consumerism of Filipino International Students in the Canadian Higher Education Institution - Jurado, Robert Paul (Global journal of Business and Integral Security, 2025)
This study delves into the experiences of international students, including Filipino students, in Canada, aiming to understand their motivations for studying abroad, the influences on their decision-making, and their overall satisfaction with the educational experience provided by Canadian institutions. Utilizing an online survey, this research collects data on various factors, including marketing strategies employed by Canadian universities, the effectiveness of support services, and the cultural adaptation process. The participant selection process is meticulously designed, leveraging university networks and social media platforms to capture a diverse and representative sample of the target group. The research highlights the impact of these factors on students’ decisions and experiences, offering valuable insights into how Canadian universities can refine their recruitment and support strategies. The findings are expected to contribute significantly to enhancing the international student experience, providing actionable recommendations for universities to better meet the needs of their international clientele and strengthen their global reputation.